THE EFFECT OF THE FINANCIAL INDEPENDENCY ON CAPITAL EXPENDITURE, INFRASTRUCTURE PERFORMANCE, ECONOMIC PERFORMANCE AND COMMUNITY WELFARE IN REGENCIES AND CITY OF BALI PROVINCE - Utama M.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
One of the functions of government is to provide services for the community, including providing infrastructure, such as roads, clean water and electricity. Infrastructure, which is often referred to as infrastructure and physical facilities, in addition to having a very strong connection with social welfare and environmental quality as well as the process of economic growth of a region. Purpose of this study to analyze the effect of local financial independency on capital expenditure, infrastructure performance, economic performance and community welfare in regencies and city in Bali Province. The data used are from secondary obtained from the Finance Bureau of Secretariat of Bali Province, and from Bali Provincial Statistics Bureau for data from 2008 to 2014. The results show that the regional financial independency has a positive effect on capital expenditure, infrastructure performance, economic performance and public welfare of the regencies and city in Bali Province. Indirectly local financial independency affects the welfare of the community in the regencies and city in Bali Province through capital expenditure, infrastructure performance, and economic performance.